TINJAUAN PERHITUNGAN, PENYETORAN, DAN PELAPORAN SPT PPH PASAL 23 ATAS ROYALTI PEMBUATAN LAGU PADA PT ABC TELEVISI - Alsala Ainum Tari (2020)
PT ABC Television is a company engaged in the media industry. Having a mission of attracting, developing, and defense of the best talents in the industry, PT ABC Television builds talent management under its side. The purpose of writing this final task is to know how to calculate, deposit, and report SPT PPh article 23 on the royalties of songwriting on PT ABC television, related documents and its implementation of the income tax ACT. Royalties of songwriting in withholding Income tax article 23 shall be charged 15% of the basis of taxation or gross amount of income for taxpayers who have a NPWP, if no NPWP is charged 100% of the policy of initial taxation. PT ABC Television made a deposit of PPh article 23 online on the page djponline.pajak.go.id with E-Billing which is used to publish Billing code for the tax deposit electronically. Generation SPT of Income tax article 23 using e-SPT application. Reporting taxes using e-Filling on the page online-pajak.com. Based on the author's analysis, the implementation of calculations, deposits and reporting of PT ABC television has been in accordance with the prevailing taxation regulations. Keywords: Article 23 Income Tax, Song Making Royalties, Calculation, Deposit, Reporting